Pengaruh Literasi Keuangan Syariah Terhadap Keputusan Memilih Bank Syariah - Ahmad Danil Azri; Siti Nurhaliza; Vina Suci Salsabila (JOURNAL OF SHARIA ECONOMICS, 2024)
Literacy is an effort made to prevent various obstacles that arise in society in accessing financial services. The level of public financial literacy has a significant impact on the success of financial inclusion efforts. Financial literacy refers to people's ability or understanding of how money works. Currently, financial literacy with sharia principles has arrived and will become a fundamental foundation for Muslims. Every Muslim individual must have knowledge of sharia finance in choosing financial services that are based on sharia principles. This research aims to determine the level of Islamic financial literacy regarding the decision to choose a Sharia Bank and determine the level of understanding and awareness of Islamic finance.